Penyertaan semula dan penawaran tenaga kerja selepas umur persaraan di kalangan ahli akademik menua di universiti awam, Malaysia - Uma, Murthy (2020)
The education sector has a growing number of academics who are aging and retiring that could eventually result in a shortage of experienced academics in various areas. On the other hand, the contribution of senior academics who specialize in specific fields is essential for the country to achieve developed nation status. Thus the objectives of this study are to identify areas where academics are in shortage, their readiness to participate after retirement, the number of hours they are willing to contribute, and methods to retain senior academics in critical areas in Public universities (PU). The respondents of this study consist of ageing academics in the age group of 55 to 60. The analysis is done using mixed methods. Qualitative method is utilised to answer the first and fourth objectives through in-depth research interviews using thematic analysis while quantitative method is used to answer the second objective through the probit model and the third objective through the Heckman model. The study found that the areas categorized as critical are medicine, dentistry, pharmacy, engineering, law, architecture, materials measurement, creative industry management, hospitality and veterinary management. Factors influencing the participation of ageing academics include income, gender, age, marital status, race, the last school attended, area of expertise, work experience, health status, academic training and pension. Factors affecting the employment of ageing academics are areas of expertise, health status and medical care. The methods of retaining those experts include government’s maximum retirement age policy, the academics own decision, availability of government funding, mentoring and buddy systems, dean’s decisions and permission to work in the private sector on part-time basis. Future studies could include all PUs especially in identifying critical areas, the involvement of all races, as well as residency factor, whether it might influence the academics participation and the number of hours they wish to offer.